2016
DOI: 10.1021/acs.jmedchem.6b00591
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plasmodium falciparum Hsp90 Contributes to the Antimalarial Activities of Aminoalcohol-carbazoles

Abstract: Malaria caused by the protozoan parasite Plasmodium falciparum (Pf) remains a major public health problem throughout the developing world. One molecular target that should receive more attention is the molecular chaperone Hsp90. It is essential and highly conserved in all eukaryotes, including in protozoan parasites. We have identified an amino-alcohol carbazole (N-CBZ) as a PfHsp90-selective inhibitor by virtually docking a large set of antimalarial compounds, previously found in a phenotypic screen, into a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
(89 reference statements)
1
45
0
Order By: Relevance
“…Plasmodium Hsp90 had been shown to regulate parasite growth in human erythrocytes [52]. Geldanamycin (GA) competitively binds to the N-terminal ATP-binding pocket of Hsp90, leading to the inhibition of its chaperone cycle and reducing the capacity of E. tenella to invade and grow in host cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium Hsp90 had been shown to regulate parasite growth in human erythrocytes [52]. Geldanamycin (GA) competitively binds to the N-terminal ATP-binding pocket of Hsp90, leading to the inhibition of its chaperone cycle and reducing the capacity of E. tenella to invade and grow in host cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that Plasmodium falciparum Hsp90 was a plausible target of carbazole aminoalcohols (Wang et al., 2016a, Wang et al., 2016b), while there is still no clue of their mechanism of action on schistosomes. In this work, three kinds of biological assay revealed a similar SAR pattern: (1) dichlorinated carbazole acted as a privileged core; (2) an alkylamine tail was beneficial for activity; conversely, arylamine substituents imparted negative effect to potency; and (3) stereochemistry of the secondary hydroxyl group had no influence on potency.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained residues were purified by recrystallization from ethanol to afford target compounds. The characterization data of compounds 6–8 and 12–16 were reported in our previous work (Wang et al., 2016a, Wang et al., 2016b), and the characterization data of compounds 3–5 , 9–11 , ( R )-7 and ( S )-7) were given as follows.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations